1999
DOI: 10.1016/s0020-7292(98)00224-0
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy and transvaginal ultrasonography in postmenopausal women with uterine bleeding

Abstract: With cut-off limit of 4 mm, TU can be considered the first choice modality of endometrial investigation in women with postmenopausal uterine bleeding to select patients at risk to carry endometrial pathology. Hysteroscopy is a more accurate technique than TU because of better specificity and must be indicated for all patients showing an endometrial strip more than 4 mm. When an endometrial thickness below 4 mm is detected by ultrasound, hysteroscopy may be indicated on clinical background because of the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
2
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 20 publications
7
35
2
8
Order By: Relevance
“…In present study, the sensitivity and specificity of TVS for suspecting endometrial pathology at ET B 4 mm were 87.09 and 75.86 %, respectively. Similar studies conducted by different investigators, Karlsson et al [2], Gull et al [3], Garuti et al [4] , Tinelli et al [5], and Kaur et al [6], had shown the sensitivity ranging from 89 to 100 % while specificity from 54.8 to 86 % at ET of 4 mm. In the present study, sensitivity, specificity, PPV, and NPV for Total 60 100…”
Section: Discussionsupporting
confidence: 64%
“…In present study, the sensitivity and specificity of TVS for suspecting endometrial pathology at ET B 4 mm were 87.09 and 75.86 %, respectively. Similar studies conducted by different investigators, Karlsson et al [2], Gull et al [3], Garuti et al [4] , Tinelli et al [5], and Kaur et al [6], had shown the sensitivity ranging from 89 to 100 % while specificity from 54.8 to 86 % at ET of 4 mm. In the present study, sensitivity, specificity, PPV, and NPV for Total 60 100…”
Section: Discussionsupporting
confidence: 64%
“…Currently, there is abundant scientific evidence (Garuti et al 1999, Bronz 2000, Litta et al 2005, Guruwadayarhalli et al 2007, Tinelli et al 2008) that hysteroscopic examination is the gold standard for the management of AUB, with curettage of the uterine cavity required only for the treatment of haemostatic urgencies and when active bleeding is present.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, office hysteroscopy could be considered a safe, well-tolerated diagnostic test that enables targeted endometrial biopsies because it accurately distinguishes normal endometrium from pathologic endometrium and has a better sensitivity, specificity, PPV and NPV than ultrasound (Garuti et al 1999, Taponeco et al 2002, Tinelli et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Office-based sampling is usually performed with disposable catheters that allow for the application of suction to obtain a specimen. Any method of sampling the endometrial cavity misses a proportion of endometrial cancers 24 (Class 1b), 47,48 (Class 3), 49 Collectively, these data would suggest that women with "nondiagnostic" endometrial biopsy specimens should have additional uterine evaluations with TVUS, contrast sonography, hysteroscopy, or a combination of any of these procedures.…”
Section: Histologic Assessmentmentioning
confidence: 99%